Spiritual Well-Being of Senior High School Students in a Non- Sectarian Private High School in Negros Island, Philippines - Macainan, Ayrton; Bual, Joel; Madrigal, Dennis (Technium Social Sciences Journal, 2025)
This study, rooted in spiritual well-being theory, assessed the spiritual well-being of students in a private non-sectarian school in Northern Negros Occidental during the 2024-2025 academic year. It examined religious and existential well-being relative to sex, religion, family monthly income, family structure, and birth order and compared their spiritual well-being across these demographics. Utilizing a quantitative, descriptive-comparative design, the research involved 75 Humanities and Social Sciences students selected through stratified random sampling. A standardized questionnaire with a high, moderate, and low scale was used, with data analyzed using mean, standard deviation, Mann Whitney, and Kruskal Wallis tests. The study adhered to the Philippine Health Research Ethics Board (PHREB) ethical standards. Generally, students reported a moderate overall spiritual well-being, characterized by high religious well-being but moderate existential well-being. Among demographic factors, a significant difference in spiritual well-being was found relative to religion, with Catholics rating significantly higher than non-Catholics. Consequently, fostering a values-based culture by integrating school values into instruction and learning opportunities is essential. The findings partially validated the spiritual well-being theory. Future research should aim for a larger scale and different contexts to further verify these assertions.